Missed diagnosis of lymphoma presenting with humoral hypercalcemia of malignancy due to cessation of oncological workup after negative computed tomography scans. Issue 12 (30th December 2021) - Altshuler, Ellery; Aryan, Mahmoud; King, William; Otero, Rolando
Abstract : Malignancy is the most common cause of hypercalcemia among hospitalised patients and is frequently caused by elevations in parathyroid hormone-related peptide (PTHrP). The most common PTHrP-producing cancers are carcinomas of the head, neck and lung. Hypercalcemia can be the presenting sign of cancer and, in these cases, solid tumours are usually discovered on CT scan. In rare cases, lymphoma may also present with hypercalcemia. CT scan is less sensitive for lymphoma than for most solid tumours and the diagnosis may be missed. We present the case of a 69-year-old woman who presented with hypercalcemia in the setting of severe weight loss and elevated PTHrP. Oncological workup was stopped after unrevealing CT scans and an underlying lymphoma was missed. Our case emphasises the need for a comprehensive oncological workup for patients with unexplained hypercalcemia and elevated PTHrP, even when CT scans are unrevealing.